1991
DOI: 10.1159/000216277
|View full text |Cite
|
Sign up to set email alerts
|

Hirudin as Anticoagulant in Experimental Hemodialysis

Abstract: After genetically engineered recombinant DNA desulfatohirudin (r-hirudin) had been investigated as to its pharmacokinetic behavior and blood level course in nephrectomized dogs, the compound was studied for its capability to prevent thrombus formation in the extracorporeal circulation. Beagle dogs underwent bilateral functional nephrectomy followed by experimental hemodialysis. r-Hirudin content in blood, fibrinogen level as well as platelet count were determined before and during the dialysis. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Hemofilters having a high cutoff are able to eliminate the hirudin within a few hours. 21 Renal elimination is considerably impaired by systemic anesthesia. Nearly all generalized anesthesia methods result in a decreased renal blood supply to different degrees.…”
Section: Figurementioning
confidence: 99%
“…Hemofilters having a high cutoff are able to eliminate the hirudin within a few hours. 21 Renal elimination is considerably impaired by systemic anesthesia. Nearly all generalized anesthesia methods result in a decreased renal blood supply to different degrees.…”
Section: Figurementioning
confidence: 99%
“…In cases where the elimination of hirudin is impaired, methods such as haemoperfusion and peritoneal dialysis can be used to remove large amounts of circulating hirudin. This is especially true of high-flux capil lary dialyzers which permit the fast elimination of the miniprotein from the body by haemodialysis (91,92). experimental DIC) is about ten times lower than that required for the inhibition of platelet aggregation-dependent thrombosis (ar terial thrombosis and platelet deposition in experimental DIC).…”
Section: Antithrombotic Effectsmentioning
confidence: 99%
“…Furthermore, r-hirudin was used for anticoagulation in experi mental haemodialysis in nephrectomized dogs (91,92). Depend ent on the permeability of the dialyzer mebranes, hirudin was eliminated during dialysis.…”
Section: Extracorporeal Circulationmentioning
confidence: 99%
“…No occlusion at doses of 40 pg/kg/min, cor responding to a plasma level of 2.5 ± 0.6 pg/ml. After studies in rats had shown that r-hirudin is able to prevent the thrombotic occlusion of an arteriovenous shunt, we studied the effect of r-hirudin in extracor poreal circulation by using it for anticoagula tion in experimental hemodialysis in nephrectomized dogs [77], After a bolus injection, the r-hirudin level decreased slowly. In con trast to untreated animals, no fibrin deposists were found in the apparatus during a 2-hour dialysis following a single r-hirudin administration of 0.5 mg. During this time, platelet counts or fibrinogen level were not significantly changed.…”
Section: Extracorporeal Circulationmentioning
confidence: 99%